2023
DOI: 10.2308/ajpt-2020-113
|View full text |Cite
|
Sign up to set email alerts
|

Critical Audit Matters: Possible Market Misinterpretation

Abstract: The Public Company Accounting Oversight Board (PCAOB) recently expanded audit reports to disclose Critical Audit Matters (CAMs) and the audit procedures used to address them. We study the first wave of CAM disclosers from July 2019 to May 2020, which included large accelerated filers reporting on their 2019 fiscal year results. We examine whether market participants erroneously perceive firms with more extensive CAM disclosures to be riskier than firms with less extensive CAM disclosures. We find that firms wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…closures and investigate the consequences of variation in these features but are largely silent on its determinants (e.g., Burke et al, 2023;Gutierrez et al, 2018;Klevak et al, 2022;Liao et al, 2022;Seebeck & Kaya, 2022;Zeng et al, 2021). 6 The International Standard on Auditing (ISA) 701 "Communicating Key Audit Matters in the Independent Auditor's Report" became effective for audits of financial statements ending on or after 15 December 2016.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…closures and investigate the consequences of variation in these features but are largely silent on its determinants (e.g., Burke et al, 2023;Gutierrez et al, 2018;Klevak et al, 2022;Liao et al, 2022;Seebeck & Kaya, 2022;Zeng et al, 2021). 6 The International Standard on Auditing (ISA) 701 "Communicating Key Audit Matters in the Independent Auditor's Report" became effective for audits of financial statements ending on or after 15 December 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In general, studies find that the number of KAMs increases with client risk and complexity (e.g. Camacho-Miñano et al, 2023;Klevak et al, 2022;Pinto & Morais, 2019;Smith, 2023). In contrast, there is inconsistent evidence for audit firm characteristics such as size, industry expertise and level of client dependence influencing the number of KAMs (e.g.…”
Section: Background and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This stream of research suggests that KAMs and other similar disclosure requirements convey little incremental information to users. However, Klevak et al (2023) reported that CAMs disclosures are associated with more volatile stock prices and dispersed analyst forecasts, suggesting that users misinterpret the disclosure of more CAMs. Porumb et al (2021) found that RMMs help lenders precisely assess borrowing risks, leading to less stringent loan contracting terms in the post-adoption period.…”
Section: Institutional Background Prior Research and Hypothesis Devel...mentioning
confidence: 99%
“…These results are consistent with those of previous studies. For example, Klevak et al (2023) reported that investors misinterpret CAMs and react negatively to disclosures. Gutierrez et al (2018), Bedard et al (2019), Lennox et al (2022) and Burke et al (2023) reported that KAMs and similar disclosures have little influence on investors and do not affect audit quality.…”
Section: Empirical Findingsmentioning
confidence: 99%